Bridging knowledge and practice in the prevention of child maltreatment in medicine: an analysis of counselling and training approaches - Anna Eberhardt; Anna Eberhardt; Ulrike Hoffmann; Ulrike Hoffmann; Jörg M. Fegert; Jörg M. Fegert; Oliver Berthold; Oliver Berthold (Frontiers in Public Health)
IntroductionProtecting children from maltreatment is an important public health challenge. Despite increasing awareness, deficits exist in the training of healthcare professionals, who play a key role in the detection of maltreatment. Initiatives such as the medical child protection helpline and the online course “Child Protection in Medicine - a basic course for all healthcare professions” have been established in Germany to improve knowledge and competence among healthcare professionals. This study examines how collaboration between the two programs contributes to strengthening expertise and practice in child protection.MethodsSince 2016, the online course has offered flexible training for healthcare professionals on child protection. From 2017, the helpline has offered free 24/7 advice for healthcare professionals on suspected cases of child maltreatment. Both measures are evaluated about effectiveness and user satisfaction. The data analysis was conducted using descriptive analyses and t tests.ResultsThe helpline received a total of 4,911 calls between 2017 and 2024, mainly from physicians (61.7%) and psychotherapists (26.4%). The number of calls continuously increased. Most calls were made during working hours. The advice provided included assessments of maltreatment cases, legal issues, and referrals. The online course was used by 3,493 health professionals. Before the training, 90.5% of the participants stated that they needed more knowledge about child protection and 95.2% requested more flexible training. After the course, knowledge improved significantly, especially among unlicensed therapists (Cohen’s d = 1.8), medical students (d = 1.5) and nurses (d = 1.5). On the other hand, action competencies increased significantly across all professional groups. Of the participants, 40.3% were familiar with the helpline before the training.DiscussionThis study finds that the helpline and the online course together strengthen professionals’ knowledge and action competencies in medical child protection. The high utilization of both services highlights existing knowledge gaps and the need for training. The increasing number of calls to the helpline underscores its relevance as a quick point of contact. The combination of individual counseling and structured training can improve child protection expertise comprehensively. An expansion of training and support services remains essential.